11.7k views
1 vote
The work of a student trying to solve the equation 4(2x − 1) = 11 + 3x + 5 is shown below: Step 1: 4(2x − 1) = 11 + 3x + 5 Step 2: 8x − 4 = 16 + 3x Step 3: 8x + 3x = 16 − 4 Step 4: 11x = 24 Step 5: x = 2.18 In which step did the student first make an error and what is the correct step?

a. Step 2: 8x − 1 = 16 + 3x
b.Step 2: 8x − 8 = 6 + 3x
c.Step 3: 8x − 3x = 16 + 4
d.Step 3: 8x + 3x = 16 − 8

User Dine
by
5.5k points

1 Answer

3 votes
step c
8x -3x =16+4
5x =20
x= 4

User Feroz Ahmed Ansari
by
6.2k points